The effect of repeated firing on shear bond and flexural strength of nickel-chromium porcelain-fused-to-metal restorations: a systematic review - Heldayani; Endang Prawesthi; Imas Maesaroh (Institut Penelitian dan Pengembangan Mandalika Indonesia (IP2MI), 2026)
Objective: This systematic review aimed to evaluate the effect of repeated porcelain firing cycles on the shear bond strength and flexural bond strength of nickel–chromium (Ni-Cr) porcelain-fused-to-metal restorations. Methods: This study followed the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. Literature searches were conducted in Scopus, Crossref, Google Scholar, and Semantic Scholar databases using Publish or Perish software version 8. The search included studies published between January 2015 and December 2025. Keywords related to repeated firing, nickel–chromium alloy, porcelain-fused-to-metal restorations, shear bond strength, and flexural strength were applied using Boolean operators. Articles were screened through title, abstract, and full-text evaluation according to predetermined inclusion and exclusion criteria. Data from eligible studies were extracted and synthesized qualitatively. Results: A total of 2,412 records were initially identified, and after the screening and eligibility process, 21 studies were included in the qualitative synthesis. The reported shear bond strength (SBS) values ranged from approximately 13 MPa to 65 MPa, depending on alloy composition, surface treatment, manufacturing technique, and firing cycles. Flexural bond strength values measured using the three-point bending test according to ISO 9693 ranged from approximately 20 MPa to 25 MPa. Most studies indicated that repeated firing cycles within the conventional clinical range had minimal influence on bond strength. However, excessive firing cycles or repeated alloy recasting could lead to gradual reductions in bond strength due to alterations in oxide layer formation and interfacial characteristics. Conclusion: Repeated porcelain firing cycles generally have limited effects on the mechanical properties of Ni-Cr porcelain-fused-to-metal restorations when performed within standard laboratory procedures. Most reported bond strength values met or approached the minimum requirements specified by ISO 9693, indicating that Ni-Cr metal–ceramic restorations remain mechanically reliable for clinical applications.